Arsenic detection in water using microfluidic detection systems based on the leucomalachite green method. Issue 42 (16th October 2019) - Lace, Annija; Ryan, David; Bowkett, Mark; Cleary, John
Abstract : This work describes the first use of microfluidic detection technology for arsenic detection in water using leucomalachite green dye. Abstract : This work describes a novel system for arsenic detection in water using leucomalachite green dye in a microfluidic platform. A simplified leucomalachite green method was integrated into a microfluidic detection system. In acidic medium arsenic is reacted with potassium iodate to liberate iodine, which in turn oxidises leucomalachite green to malachite green forming a green colour associated with an absorbance band in the visible region ( λ max = 617 nm). A 1 : 1 v/v sample to reagent ratio was used for the analysis. Syringe pumps were used to introduce and transport reagents and samples into a PMMA microfluidic detection chip. The optical detection system consisted of a LED light source with a photodiode detector. The modified method can determine arsenic over the linear range of 0.3–2 mg L −1 with a limit of detection of 0.32 mg L −1 . The average % RSD and recovery were 21.1% and 93.7%, respectively. The sample run time was optimised to 25 minutes. A range of environmental water samples were analysed using the modified method.